2004
DOI: 10.1002/jmri.20130
|View full text |Cite
|
Sign up to set email alerts
|

Reliability in detection of hemorrhage in acute stroke by a new three‐dimensional gradient recalled echo susceptibility‐weighted imaging technique compared to computed tomography: A retrospective study

Abstract: Purpose:To compare the sensitivity of magnetic resonance (MR) susceptibility-weighted imaging (SWI) with conventional MR sequences and computed tomography (CT) in the detection of hemorrhage in an acute infarct. Materials and Methods:A series of 84 patients suspected of having acute strokes had both CT and MR imaging (MRI) scans with diffusion-weighted imaging (DWI) and SWI. The SWI sequence is a new high-resolution three-dimensional (3D) imaging technique that amplifies phase to enhance the magnitude contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 13 publications
3
80
0
2
Order By: Relevance
“…Uncoupling between oxygen supply and demand in hypoperfused tissue may cause a relative increase of deoxyhemoglobin levels and a decrease of oxyhemoglobin in the tissue capillaries and the draining veins. Therefore, SWI has been applied to various pathologies of the brain that affect magnetic inhomogeneity, such as stroke, 8,11 trauma, 8 cerebral cavernous malformation, 12,13 arteriovenous malformation, 14 dural arteriovenous fistula, 15 pathophysiology affecting iron storage conditions, [16][17][18] brain tumor, 19 and cerebral amyloid angiopathy. 20 It is noteworthy that this method has the potential to demonstrate increased oxygen extraction in focal cerebral ischemia.…”
Section: Betweenmentioning
confidence: 99%
“…Uncoupling between oxygen supply and demand in hypoperfused tissue may cause a relative increase of deoxyhemoglobin levels and a decrease of oxyhemoglobin in the tissue capillaries and the draining veins. Therefore, SWI has been applied to various pathologies of the brain that affect magnetic inhomogeneity, such as stroke, 8,11 trauma, 8 cerebral cavernous malformation, 12,13 arteriovenous malformation, 14 dural arteriovenous fistula, 15 pathophysiology affecting iron storage conditions, [16][17][18] brain tumor, 19 and cerebral amyloid angiopathy. 20 It is noteworthy that this method has the potential to demonstrate increased oxygen extraction in focal cerebral ischemia.…”
Section: Betweenmentioning
confidence: 99%
“…Several recent studies have shown that the use of MRI signal phase in gradient-echo (GRE) MRI can improve contrast MRI in specific human brain structures, including veins and iron-rich regions (10)(11)(12)(13)(14). Preliminary studies have also shown a substantial contrast between WM and cortical GM (11,15).…”
mentioning
confidence: 99%
“…Previous investigators have shown that SWI is more sensitive than conventional MR imaging sequences or CT for detecting foci of hemorrhages. 5 In this case, SWI detected more foci of hemorrhages than conventional sequences. Because conventional MR imaging showed faint signal changes at the corresponding locations of the foci of the hemorrhage without parenchymal edema, the foci of the hemorrhage may be chronic.…”
Section: Discussionmentioning
confidence: 61%